PENINGKATAN LITERASI FINANSIAL DAN BISNIS UNTUK MENINGKATKAN KINERJA UMKM DESA WISATA BALI - Anies Lastiati; Rizka Ramayanti (LP2M Universitas Hasanuddin, 2023)
Despite absorbing most of the available workforce in Indonesia, the Micro, Small, and Medium Industries (MSMEs) sector still needs to perform optimally. The MSME sector contributes only around 61% of national income. The government has been promoting some MSME development programs, which are carried out in clusters and working groups. In line with the government initiatives, the purpose of this community service is to improve the financial literacy of MSME owners, specifically by providing knowledge for them to be able to prepare business documents. The audience of this Business Planning Workshop was 32 MSMEs owners who are members of the MSME development cluster of the Bali Provincial Tourism Village Communication Forum. The result, which is the conclusion of this community service, is that all MSME participants can prepare the Business Plan documents needed to be submitted by MSMEs for their fund to seek purposes. In general, the participants' assessment of this service program is helpful for their business, exciting, and straightforward. — Industri Mikro Kecil dan Menengah (UMKM) di Indonesia, meski menyerap sebagian besar tenaga kerja yang tersedia, namun masih belum dapat berkinerja dengan optimal. Terbukti sektor UMKM ini baru mampu menyumbang sekitar 61% pendapatan nasional. Salah satu cara yang dilakukan oleh pemerintah adalah dengan melakukan pembinaan UMKM dalam kluster-kluster dan kelompok-kelompok kerja. Tujuan pengabdian ini adalah meningkatkan kemampuan literasi finansial para pelaku UMKM, secara khusus dengan memberikan pengetahuan dalam penyusunan perencanaan bisnis lewat workshop. Audiens Workshop Perencanaan Bisnis ini adalah 32 UMKM yang tergabung dalam kluster pembinaan UMKM Forum Komunikasi Desa Wisata Provinsi Bali. Hasilnya yang merupakan simpulan pengabdian ini adalah pelaku UMKM mampu menyusunan dokumen Business Plan yang dibutuhkan untuk diajukan oleh UMKM saat mencari sumber permodalan. Secara umum penilaian peserta terhadap program pengabdian ini adalah bermanfaat untuk usahanya, menarik dan jelas.